2017
DOI: 10.1038/srep45524
|View full text |Cite|
|
Sign up to set email alerts
|

Cochlear gene therapy with ancestral AAV in adult mice: complete transduction of inner hair cells without cochlear dysfunction

Abstract: The use of viral vectors for inner ear gene therapy is receiving increased attention for treatment of genetic hearing disorders. Most animal studies to date have injected viral suspensions into neonatal ears, via the round window membrane. Achieving transduction of hair cells, or sensory neurons, throughout the cochlea has proven difficult, and no studies have been able to efficiently transduce sensory cells in adult ears while maintaining normal cochlear function. Here, we show, for the first time, successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
137
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 49 publications
11
137
3
Order By: Relevance
“…Nevertheless, improving the large transgene reconstitution efficacy by simply increasing the amount of available vector genomes does not improve protein expression levels as shown for dual‐AAV vectors in the retina (Carvalho et al , ). Since the IHC transduction rates of our single AAV2/6 eGFP‐expressing virus reached 99%, it is unlikely that other AAV serotypes such as AAV2/Anc80 (Landegger et al , ; Suzuki et al , ) will increase the amount of fully functional otoferlin protein levels in IHCs.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, improving the large transgene reconstitution efficacy by simply increasing the amount of available vector genomes does not improve protein expression levels as shown for dual‐AAV vectors in the retina (Carvalho et al , ). Since the IHC transduction rates of our single AAV2/6 eGFP‐expressing virus reached 99%, it is unlikely that other AAV serotypes such as AAV2/Anc80 (Landegger et al , ; Suzuki et al , ) will increase the amount of fully functional otoferlin protein levels in IHCs.…”
Section: Resultsmentioning
confidence: 95%
“…Semicircular canal injection was done following (Suzuki et al, 2017) using AAV2-retro-CAG-GFP (1.0E13 GC/ml,Janelia Farm), AAV2-retro-CAG-tdTomato (7.0E12 GC/ml, Addgene) or AAV-PHP.S-CAG-tdTomato (1.7E13, Addgene) (Chan et al, 2017) under isoflurane anesthesia. Briefly, a small hole we bored into the posterior semicircular canal using a 27 ga needle.…”
Section: Viral Injectionsmentioning
confidence: 99%
“…However, two of the nine treated mice exhibited a remarkably lower threshold at 32 kHz, suggesting that the treatment improved their sensitivity to higher frequency sounds (Figure S6A). Although functional rescue was not statistically significant due to the inherent variability of the treatment to P2 mice (Isgrig et al, 2017; Suzuki et al, 2017), immunofluorescence analysis revealed more inner hair cells in treated cochlea than those of untreated cochlea (Figures S6B–S6D). The hair cells at the cochlear base are tonotopically tuned for high-frequency sounds (Davis and Silverman, 1970).…”
Section: Resultsmentioning
confidence: 98%
“…To test whether the myo-tail vector could complement the mutation in cochlear hair cells, which are responsible for auditory sensation, the vector was injected into the posterior semicircular canal at P2 (Isgrig et al, 2017; Suzuki et al, 2017), and the mice were examined for auditory brainstem response (ABR) at 3 months of age. The mice displayed more severe auditory deficits when responding to higher frequency sound, because a significantly elevated ABR threshold was detected in all untreated mice when a 32-kHz stimulus was given (Figure S6A).…”
Section: Resultsmentioning
confidence: 99%